Pengaruh Kemudahan Aplikasi E-Commerce Terhadap Minat Belanja Masyarakat - Esra Fania Silitonga; Steven I.S.M Marbun; Mhd. Fajar Nasution; Alintia Silitonga (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the effect of ease of use of e-commerce applications on public shopping interest. The research employs a quantitative descriptive approach with data collected through questionnaires distributed to 12 respondents dominated by individuals aged 17–20 years. The results indicate that ease of use plays a crucial role in shaping shopping interest in e-commerce platforms. Data show that 91.7% of respondents perceive e-commerce applications as easy to understand, while 100% of respondents state that these applications are very helpful in shopping activities. In addition, all respondents report ease in finding products and completing payment processes, each reaching 100%. These findings suggest that simple navigation, clear features, and efficient transaction systems contribute to positive shopping experiences. The dominance of Shopee usage (66.7%) compared to TikTok Shop (33.3%) further reflects consumer preference for platforms offering convenience and comfort. Overall, the study concludes that the ease of e-commerce applications significantly influences shopping interest by creating positive shopping experiences, increasing consumer confidence, and encouraging repeated use, particularly among young and digitally literate users.